May Measurement Month 2019: an analysis of blood pressure screening results from China. (20th May 2021) - Chen, Xin; Liu, Chang-Yuan; Xu, Li-Ying; Wang, Hong-Yu; Liu, Min; Zhang, Yu-Qing; Yin, Xin-Hua; Wang, Xiao-Long; Yu, Jing; Li, Wei-Hua; Beaney, Thomas; Xia, Xin; et al.
Abstract: To report the blood pressure (BP) data obtained in the May Measurement Month (MMM) 2019 in China. Study participants were recruited if ≥18 years of age and had ideally not had their BP measured for ≥1 year. BP was measured three times consecutively with a 1-min interval in the sitting position, using a validated electronic BP monitor. Trained volunteer investigators administered a questionnaire to collect information on lifestyle, medical history, and use of medications. The measurement was performed in 238 387 participants in 250 sites across 31 China provinces. The majority of screening took place in hospitals or clinics (78.7%), with 17.1% in outdoor public areas and 4.2% in other settings. The study participants included 127 853 women (53.6%) and had a mean (±SD) age of 48.9 ± 16.2 years. The mean (of readings two and three) systolic/diastolic BP was 121.8/73.8 mmHg. In all hypertensive patients ( n  = 66 181, 27.8%), the awareness, treatment, and control rates of hypertension were 51.5%, 48.4%, and 29.1%, respectively. Linear regression models showed differences in systolic and diastolic BP according to sex and age and several other major characteristics, such as previous stroke, myocardial infarction, and diabetes mellitus, antihypertensive medication use and known hypertension, previous hypertension in pregnancy and current pregnancy, alcohol intake and current smoking, and body mass index. The MMM 2019 campaign has been successful in measuring BP in a large member of participants in China.